Calidad de las raices de yuca y factores que intervienen en ella - Wheatley, Christopher C. (International Center for Tropical Agriculture, 1991)
The most important quality factors are identified for each end use given to cassava (human consumption, animal consumption, starch production). Information available on the effects of harvest time, plant age, soil/climatic factors, and abiotic factors (pests and diseases) on cassava quality parameters is reviewed. Future areas of research are also indicated. The importance of quality, not only from the viewpoint of the farmer but also from the viewpoint of the consumer (human or animal), for all cassava products and forms is highlighted. Plant breeders should therefore include quality assessment as a screening parameter; since most of these factors, especially for human consumption, are subjective and difficult to assess and since soil, climatic and biotic factors greatly influence quality, multiple assessments under different regimes are required to assure quality stability. (CIAT)